Analisis Daya Saing Komoditas Bawang Merah di Desa Songan B Kecamatan Kintamani Kabupaten Bangli - CHRISTHOPER, MICHAEL GEORGE; YUDHARI, I DEWA AYU SRI; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Analysis of the competitiveness of the shallot commodity in Songan B Village, Kintamani District, Bangli Regency Shallots are one of the commodities in horticulture sector. Shallots have been one of the main commodities of horticultural products cultivated by farmers in Indonesia for a long time. Shallots have long been cultivated by people in Bali specially in Bangli Regency. The purpose of this study was to determine how much competitiveness the shallot commodity has in Songan B Village, by calculating the amount of competitive advantage and comparatif advantage. Sample determination technique using Purposive Sampling technique. Sample that use in this research is farmer of Songan B village who are working on farming a who cultivating shallots selected with a total of 46 shallot farmers. Data collection was carried out from August to October 2022 in Songan B Village, Kintamani District, Bangli Regency. The analytical tools used to calculate competitive and comparative advantages are Policy Analysis Matrix with Private Cost Ratio and Domestic Resources Cost as indicators. Research results shows that shallots farming in Songan B Village has competitiveness in the form of competitive advantage and comparatif advantage, and also can compete nationally and globally, with a PCR indicator worth 0.225674947 which means it has a competitive advantage, and the DRC indicator is worth 0.323329213 which means it has a comparative advantage.